The mommy wars: on the home front and waged abroad. Issue 5 (2nd September 2016) - Steiner, Linda; Lachover, Einat
Abstract: Anne-Marie Slaughter's Atlantic article "Why Women Still Can't Have It All, " published in 2012, generated huge response, well beyond what already has become typical in the intensifying mommy wars in the United States. It also drew considerable attention globally. Within one week of publication, Slaughter's "lament" attracted a million readers. Slaughter's explanation of why she quit her high powered job, and then Yahoo's choice of the then-pregnant Marissa Mayer as its new chief executive, provoked another round of mommy wars. The research reported here on how journalists dealt with the controversy compares the US, with its tradition of heated controversy over working mothers and neoliberal opposition to structural supports for families, and Israel, where attention to Slaughter was somewhat surprising, given the presumption in Israel that mothers will work outside the home. Journalistic discourse in both countries tended to frame the work–home conflict as a women's issue, to be addressed by women journalists, and not men. Moreover, writers tended to address the issue anecdotally, in terms of personal experience but ignoring structural issues and structural solutions and ignoring how solutions for middle-class professional women or women at the "center" may not work for other kinds of women.